2018
DOI: 10.3389/fgene.2018.00320
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Analysis Identifies p53 as a Candidate Prognostic Biomarker for Neuropathic Pain

Abstract: Neuropathic pain (NP) is a type of chronic pain that is different from the common type of pain. The mechanisms of NP are still poorly understood. Exploring the key genes and neurobiological changes in NP could provide important diagnostic and treatment tools for clinicians. GSE24982 is an mRNA-seq dataset that we downloaded from the Gene Expression Omnibus database to identify key genes in NP. Differentially expressed genes (DEGs) were identified using the BRB-ArrayTools software and R. Functional and pathway … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…Spinal cord cell apoptosis reported is observed during the development of neuropathic pain [18,19]. Whiteside et al [40] found that the development of chronic constriction injury-induced neuropathic pain is associated with increased apoptosis in spinal cord cells, which is thought to be the cause of pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spinal cord cell apoptosis reported is observed during the development of neuropathic pain [18,19]. Whiteside et al [40] found that the development of chronic constriction injury-induced neuropathic pain is associated with increased apoptosis in spinal cord cells, which is thought to be the cause of pain.…”
Section: Discussionmentioning
confidence: 99%
“…In neuropathic pain, spinal cord cells can undergo apoptosis [18,19], which is closely related to the p38 MAPK pathway [20,21]. Therefore, we hypothesized that PKA is involved in neuropathic pain by activating the p38MAPK pathway to mediate spinal cord cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Spinal cord cell apoptosis reportedly is observed during the development of neuropathic pain [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…In neuropathic pain, spinal cord cells can undergo apoptosis [17,18], and apoptosis is closely related to the p38 MAPK pathway [19,20]. Therefore, we hypothesized that PKA is involved in neuropathic pain by activating the p38MAPK pathway to mediate spinal cord cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…The basic properties of differentially expressed proteins were analyzed using Gene Ontology (GO) and protein-protein interaction network at Metascape (https://metascape.org/gp/ index.html) and STRING (https://string-db.org/), respectively (23,24).…”
Section: Bioinformatics Analysismentioning
confidence: 99%